2024
DOI: 10.1002/cnl2.116
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical alcohol oxidation reaction on Precious‐Metal‐Free catalysts: Mechanism, activity, and selectivity

Jiawei Shi,
Jun Ma,
Enze Ma
et al.

Abstract: The electrochemical alcohol oxidation reaction (AOR) is pivotal for the development of sustainable energy. The complete oxidation of alcohols has attracted extensive attention as a vital process in fuel cells. Moreover, as an alternative reaction to the oxygen evolution reaction, the selective oxidation of alcohols emerges as an effective means to lower the energy expenditure associated with electrolytic hydrogen production while yielding high‐value products. Nonprecious metal materials have been widely applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 121 publications
0
1
0
Order By: Relevance
“…Previous studies based on the density functional theory (DFT) calculations have also revealed a similar reaction pathway for the oxidation of BA to Ph-COOH. 53–57 The rate determining step during BA oxidation was determined to be the conversion of Ph-COH* to Ph-COOH 53–57…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies based on the density functional theory (DFT) calculations have also revealed a similar reaction pathway for the oxidation of BA to Ph-COOH. 53–57 The rate determining step during BA oxidation was determined to be the conversion of Ph-COH* to Ph-COOH 53–57…”
Section: Resultsmentioning
confidence: 99%